SNX10 in autosomal recessive osteosclerosis, osteosarcoma, rheumatoid arthritis, and osteoporosis: molecular mechanisms and therapeutic implications - Liu, Sijia; Deng, Huili; Liu, Junjie; Zhang, Jun; Chen, Xier; Zhou, Xuchang; Zheng, Chengqiang (Frontiers in Cell and Developmental Biology, 2025)
Bone metabolic diseases are typically caused by abnormal cell metabolism and cell death within the bone, involving cell types such as osteoblasts, osteoclasts, osteocytes, chondrocytes, and bone marrow mesenchymal stem cells. Bone metabolic diseases include autosomal recessiveosteosclerosis (ARO), osteosarcoma (OS), rheumatoid arthritis (RA), and osteoporosis (OP). However, there are other categories of bone metabolic disorders in addition to the four mentioned in this review, including, but not limited to, osteochondrosis, Paget’s disease, and hyperparathyroidism-associated bone disease, and others. The incidence of bone metabolism-related diseases has gradually increased over time and social changes, affecting a wider and wider group of people. Therefore, systematically analyzing the molecular pathological mechanisms of bone metabolic diseases, particularly the spatiotemporal dynamics of key regulatory nodes, has become an urgent need for developing novel therapeutic strategies. It is important to note that strictly speaking OS and RA are not usually categorized as bone metabolic disorders. However, this review categorizes them as bone metabolic diseases because of the pathological mechanisms, cellular metabolic abnormalities, and clinical evidence explored in OS and RA. Both OS and RA fit the basic profile of bone metabolic diseases. SNX10, as a member of the sorting nexin family, exerts unique regulatory functions in membrane transport through its phospholipid-binding properties mediated by the PX (phox homology) domain. Recent mechanistic analyses have shown that SNX10 exhibits multidimensional therapeutic potential in bone metabolic diseases by regulating pathways such as vesicle transport, lysosome maturation, and RANKL signal transduction. This review systematically integrates the latest research evidence on SNX10 in bone metabolic diseases, focusing on elucidating its molecular regulatory networks in conditions such as ARO, OS, RA, and OP, aiming to provide a theoretical basis for the application of SNX10-targeted precision therapeutic strategies in bone metabolic diseases.